Perception of Justice, Post Service Recovery Satisfaction, Intention to Revisit and Wom Recommendations of Foreign Tourists Visiting Bali - Sudiarta, I Nyoman; Sri Suprapti, Ni Wayan; Sukaatmadja, I Putu Gde (E-Journal of Tourism; Volume 1 Number 1 (March 2014), 2014)
This study aimed to determine the effect of perceptions of distributive, procedural and interactional justice on post-service recovery satisfaction and post-service recovery satisfaction effect on the intention to revisit and WOM recommendations of foreign tourists to Bali. The respondents of this study were foreign tourists who visited Bali and ever experienced complaint. The number of eligible samples was 100 respondents. The questionnaire was given to tourists visiting tourist attractions of Tanah Lot, Kintamani and Besakih. Data were analyzed using multivariate statistical analysis, namely structural equation modeling (SEM). The results of this study indicated that the perception of distributive justice, procedural and interactional had a positive and significant effect on the post-service recovery satisfaction of foreign tourists who visited Bali. The study also found a positive and significant effect of post-service recovery satisfaction on the intention to revisit and the intention of recommending positive WOM of foreign tourists who visited Bali.
Keywords: distributive justice, procedural, interactional, service recovery satisfaction, intention to revisit, WOM recommendations, foreign tourists, Bali.